Discourses on gender and sexual inequality : the legacy of Sandra L. Bem - Kohlman, Marla H.; Krieg, Dana B. (Advances in gender research ;, 2017)
This edited collection examines the significance of Sandra L. Bem's research for current debates on gender and gender roles in the social sciences, with contributions that question how the institution of gender has been, and remains, deeply contested.